KEPASTIAN HUKUM PENGUASAAN TANAH ADAT OLEH DESA PAKRAMAN TUSAN BANJARANGKAN - A.A. Mas Adi Trinaya D (Fakultas Hukum Universitas Dwijendra, 2019)
The settlement of village yard disputes the village head and customary bendesa play a very important role. Village Head and Bendesa Adat as the interpreter of peace is very reasonable, still included within the boundaries of its duty to make the people of their village to live in peace and peace. In view of the root of the problem, a dispute or violation of the law may be a case of pure custom, a non-custom case, or a mixed case (custom case + non-adat). Included in the category of indigenous cases are disputes whose objects are customary issues or violations which according to local dresta are disgraceful acts but not regulated in the laws and regulations of the State for example are disputes / violations relating to fathers (customary duties), Prohibition of burying corpses in setra, kasepekang case, lokika sanggraha, wrong timpal and others Thus legal certainty of customary land tenure in pakraman village is important to do because nowadays there are often conflicts of villagers pakraman back ground about the land starting from the land of inheritance, land Village yard and village wasteland (AYDS). Above the above, the authors are interested to conduct research by taking the title: